Core-substituted naphthalene diimides: influence of substituent conformation on strong visible absorption - Quinn, Samuel; Davies, E. Stephen; Pfeiffer, Constance R.; Lewis, William; McMaster, Jonathan; Champness, Neil R. (Wiley, 2017)
Substitution of the aromatic core of naphthalene diimide (NDI) chromophores by morpholine leads to molecules with strong absorbance in the visible spectrum. The shift of absorption maxima to lower energy is determined not only by the degree of substitution but also by the relative conformation and orientation of the tertiary amine with respect to the plane of the NDI.